1992
DOI: 10.1111/j.1467-1770.1992.tb01043.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Native Speaker Judgments of Nonnative Pronunciation and Deviance in Segmentais, Prosody, and Syllable Structure

Abstract: This study investigated the relationship between experienced SPEAK Test raters' judgments of nonnative pronunciation and actual deviance in segmentals, prosody, and syllable structure. Sixty reading passage speech samples from SPEAK Test tapes of speakers from 11 language groups were rated impressionistically on pronunciation and later analyzed for deviance in segmentals, prosody, and syllable structure. The deviance found in each area of pronunciation was then correlated with the pronunciation ratings using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
278
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(293 citation statements)
references
References 39 publications
10
278
0
5
Order By: Relevance
“…Hahn (2004) and Anderson-Hsieh et al (1992), referred to earlier in this chapter, are two examples of such studies.…”
Section: Intel/igibility and The Ita Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Hahn (2004) and Anderson-Hsieh et al (1992), referred to earlier in this chapter, are two examples of such studies.…”
Section: Intel/igibility and The Ita Contextmentioning
confidence: 99%
“…The speech samples utilized in the Anderson-Hsieh et al (1992) were rating using the pronunciation subtest of the SPEAK test, given the way they were required to listen to and ~valuate the speech.…”
Section: Intel/igibility and The Ita Contextmentioning
confidence: 99%
“…The prosodic research has shown that not only segmental but also suprasegmental features contribute to perceived accentedness (Anderson-Hsieh, Johnson and Koehler 1992;Derwing and Munro 1998;Derwing and Rossiter 2003;Field 2005). For instance, in a study aimed at describing the general relevance of prosody to the perception of a foreign accent Jilka (2000) confirmed its significance in a series of experiments using low-pass filtered stimuli on German-accented English and Englishaccented German.…”
Section: Introductionmentioning
confidence: 94%
“…Comparative studies of L1 and L2 discourse structure focus on a variety of features of the intonation production of learners and demonstrate crucial differences in the use of prosodic cues by L2 speakers (Anderson-Hsieh, Johnson, & Koehler, 1992;Pickering, 2001;Tyler et al, 1988;Tyler & Davies, 1990;Wennerstrom, 1997). In a study investigating 30 intermediate learners from three L1 backgrounds performing a read-aloud task, Wennerstrom (1994) found that while Spanish L2 speakers and a native speaker control group marked a new topic with a high pitch onset, Thai and Japanese L2 learners demonstrated no paragraph initial pitch change.…”
Section: Intonational Paragraphs In L1 and L2 Academic Discoursementioning
confidence: 99%